2015
DOI: 10.15283/ijsc.2015.8.2.209
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Stem Cells Transplantation in Egyptian Patients with Liver Cirrhosis on Top of Hepatitis C Virus

Abstract: Background and ObjectivesUse of pluripotent stem cells is an ideal solution for liver insufficiencies. This work aims is to evaluate the safety and feasibility of autologous stem cells transplantation (SCT) in Egyptian patients of liver cirrhosis on top of hepatitis C virus (HCV).Subjects and Results20 patients with HCV induced liver cirrhosis were divided into 2 groups. Group I: included 10 patients with liver cirrhosis Child score ≥9, for whom autologous stem cell transplantation was done using granulocyte c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…The blood counts varied slightly after the procedure but no significant cytopenias were noted. The duration of response has been significant and longer than reported in the literature (12)(13)(14).…”
Section: Case Presentationmentioning
confidence: 48%
See 2 more Smart Citations
“…The blood counts varied slightly after the procedure but no significant cytopenias were noted. The duration of response has been significant and longer than reported in the literature (12)(13)(14).…”
Section: Case Presentationmentioning
confidence: 48%
“…They reported improvement of the liver function tests and stabilization of the liver-related symptoms over the following 6 months (12). Al Tayeb et al showed efficacy and safety of autologous stem cell transplantation in patients with liver cirrhosis related to hepatitis C infections (13). Yannaki et al proved the safety and efficacy of mobilized peripheral blood stem cells (PBSCs) Figure 1 The variation of the liver parameters over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCV infection alters lipid metabolism and leads to dyslipidemia, hepatic steatosis and advanced fibrosis . Persistent viral infections tend to induce liver dysfunction and may further result in cirrhosis and hepatocellular carcinoma . Hepatic steatosis is one of the primary aetiologies of induced liver diseases.…”
Section: Introductionmentioning
confidence: 99%
“…3 Persistent viral infections tend to induce liver dysfunction and may further result in cirrhosis and hepatocellular carcinoma. 4,5 Hepatic steatosis is one of the primary aetiologies of induced liver diseases. Compared to other chronic liver diseases, the occurrence of hepatic steatosis is prevalent in patients with chronic hepatitis C. 6 The core protein of HCV localizes to the surface of lipid droplets and contributes to hepatic steatosis by interfering with intracellular lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%